Innovative treatment approaches in forensic and correctional settings - Siglag, Michael (International perspectives on forensic mental health, 2024)
"This book describes targeted therapeutic interventions, programmatic approaches, and system-wide transformations of forensic mental health services. Interventions include creative applications of a variety of multidimensional and theoretically grounded approaches. These include variations of cognitive behavioral therapy (CBT), dialectical behavior therapy (DBT), psychodynamic, psychosocial, Risk-Needs-Recovery and Good Lives Models, and other approaches. An international team of contributors address key topics such as: aggression, sexual violence, substance use, trauma informed care, competency restoration, and other specialized treatment areas. Clinical examples are included throughout, which include current data and research, and suggestions for further research for use by clinicians working in a range of settings with a variety of treatment population subsets. This book is essential for administrators and clinicians seeking effective and state-of-the-art approaches"--